Respon Tanaman Jagung Hibrida (Zea mays L.) terhadap Pemberian Pupuk Hayati Mikoriza di Lahan Pasang Surut - Marlina, Neni; Amir, Nurbaiti (Seminar Nasional Lahan Suboptimal, 2019)
Marlina N, Amir N. 2019. Response of hybrid maize (Zea mays L.) to giving mycorrhizal biofertilizer in tidal land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 325-329. Palembang: Unsri Press. Growth and production of hybrid maize plants in tidal land can be improved by the provision of mycorrhizal biofertilizer. Mycorrhizal biofertilizer and chicken manure organic fertilizer are very helpful in providing nutrients in nitrogen, phosphorus and potassium in tidal land which has a low nutrient content. Research on mycorrhizal biofertilizer   has been carried out in the farms of Purwosari village, Tanjung Lago District, Banyuasin Regency, South Sumatra Province. The research objective   was to study  a dose of mycorrhizal biofertilizer   which is suitable for increasing hybrid corn production. The research period was conducted from July to Nopember 2018. This study used a  Group Randomized Design with 3 of treatments and 9 groups. The dose of mycorrhizal biofertilizer is 3, 5 and 7 g/plant. The results showed that hybrid corn plants had a positive response with the giving of 7 g/plant mycorrhizal biofertilizer  which was indicated by the production of 4,70 kg/plot.Keywords: mycorrhizal biofertilizer, hybrid maize and tidal land